Blending poly(butylene succinate) with poly(lactic acid): Ductility and phase inversion effects. (October 2015) - Deng, Y.; Thomas, N.L.
Graphical abstract: Highlights: PBS is not miscible with PLA to any substantial extent, but compatibility is achieved at low addition levels (20 wt%). Elongation-to-break increased to over 250% with as little as 10 wt% of PBS added. PLA and PBS formed a co-continuous phase in the composition range of 8–42 wt% of PBS. The theoretical value of the phase inversion point calculated from viscosity measurements was 8.4 wt%. Abstract: Synergistic effects of blending two bio-based, bio-degradable polymers, poly(butylene succinate) (PBS) and poly(lactic acid) (PLA) are investigated. A series of melt-blended compounds were prepared at PBS/PLA weight ratios of 0/100, 10/90, 20/80, 40/60, 60/40, 80/20 and 100/0. Thermal properties, crystallinity, melt viscosities, mechanical properties and phase morphology were studied. There was found to be a dramatic improvement in ductility, over 250% elongation-to-break, with as little as 10 wt% of PBS added. This was shown to be due to a co-continuous phase morphology, which was determined by the relative viscosities of the components.